Transconstitucionalism: from a structural coupling to the transversal rationality (Revista da Faculdade de Direito, Universidade de São Paulo, 2013)
The idea of transconstitucionalism represents a milestone in innovative proposals in constitutional law. It is a perspective that seeks to demonstrate how the context of “world society” (Weltgesellschaft) develops new mechanisms for exchanging experiences constitutional at the local, national, regional and international levels. Furthermore, the transconstitucionalism model breaks with the famous and worn debate between monists and pluralists in international law. The author’s proposal seeks to overcome the idea of constitution as luhmannian structural coupling to allow for a more adequate for new situations faced. So if makes use of the concept of “cross rationality”, which would be more able to cope with the analysis of the conditions of transconstitucionalism. However, the proposal is not without limitations. As the author of the theory notes, is not free of obstacles imposed by empirical conditions of world society.